-2(3x+4)+x=-5x+17

Simple and best practice solution for -2(3x+4)+x=-5x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x+4)+x=-5x+17 equation:



-2(3x+4)+x=-5x+17
We move all terms to the left:
-2(3x+4)+x-(-5x+17)=0
We add all the numbers together, and all the variables
x-2(3x+4)-(-5x+17)=0
We multiply parentheses
x-6x-(-5x+17)-8=0
We get rid of parentheses
x-6x+5x-17-8=0
We add all the numbers together, and all the variables
-25!=0
There is no solution for this equation

See similar equations:

| (1)/(5)(2x-15)=(1)/(10)(4x-30) | | -10q=-8-9q | | -7u-7=6u-7 | | 6x+20=92−6x | | 0.4+0.5=0.7x-0.7 | | 5n+24+3n+20=180 | | -3|x|=-18 | | -3x-8=-5x+10 | | 23x-5=9 | | 3(n+1)=9(3n-5) | | 3=0.5x+15 | | 8x+6=4(x+4)+2(2x-5) | | -6x+8=44. | | -8+p/2=-11 | | -16=3-m | | 12x-28+6x-21=4x+1 | | 6=5y-20 | | -4r+8=-2-4r+r | | -7+5g=2+6g | | 313.72=160+0.61x | | -15x40=23-8x | | 15x+3=-36-18x | | 8x+96=2.4x | | 52+6x+9+2x+23=180 | | 20-2x=x+20 | | -3.1s=-1922 | | 9x-16=31 | | 2(1x+-8)=10 | | 3x+24=32 | | -6j-9=-6j+9 | | 5y-y=-28 | | g=2g+7 |

Equations solver categories